PENGARUH PEMBELAJARAN PROJECT BASED LEARNING TERHADAP KEMAMPUAN PSIKOMOTORIK CALON GURU SD PADA MATERI WUJUD BENDA DAN PERUBAHANNYA - Nurul Hidayah; Dwi Swastanti Ridianingsih; Harun Arrasyid (Biro 3 Kemahasiswaan dan Kerjasama Universitas Abduracman Saleh Situbondo, 2026)
The aim of this study was to determine the effect of implementing the Project Based Learning (PjBL) model on the psychomotor abilities of prospective elementary school teachers on the topic of the states of matter and their changes. This study involved 9 students from the Elementary School Teacher Education Study Program (Pendidikan Guru Sekolah Dasar/PGSD). The research employed a quantitative approach, with data collected through an observation sheet used to assess students’ psychomotor abilities during the learning process. The assessed aspects included the abilities to collect information, observe, experiment, associate, and communicate. The results showed that the implementation of the Project Based Learning model produced positive outcomes for students’ psychomotor abilities. The average score for the collecting information aspect was 3.67 with a percentage of 91.67%, the observing aspect obtained an average of 3.56 with 88.89%, and the experimenting aspect achieved the highest average of 3.72 with 93.06%, all categorized as very good. Meanwhile, the associating aspect obtained an average score of 2.50 with 62.50%, and the communicating aspect obtained 2.39 with 59.72%, both categorized as sufficient. Based on these results, it can be concluded that the Project Based Learning model has a positive influence on the psychomotor abilities of prospective elementary school teachers in learning about the states of matter and their changes, particularly in improving skills related to conducting practical activities, observations, and information gathering during the learning process.